Hijab Behind the Scenes: Analysis of Qur’anic Interpretation in Traditional Arab Clothing - Syakhna Izzatunnisa; Muhammad Kudhori (Jurnal test, 2025)
The hijab occupies a central place in traditional Arab clothing, carrying historical, religious, and social dimensions. Within Islam, it is closely linked to the principles of modesty and the construction of Muslim women’s identity, though its practice and interpretation have evolved over time. This study explores Qur’anic interpretations of the hijab and traces its historical development while also examining the impact of social, political, and cultural contexts on its use. Employing a qualitative approach through a literature-based analysis of primary and secondary sources, the research highlights that the hijab functions not only as a religious symbol but also as a marker of cultural identity and, at times, as a form of resistance to Western hegemony. Diverse scholarly interpretations have given rise to variations in hijab practices across the Arab world and the broader Muslim community. Furthermore, ongoing debates in relation to feminism and women’s rights demonstrate that the hijab remains a dynamic and contested discourse, continually reshaped by changing societal contexts.